PENGARUH TERAPI MUROTAL AL-QUR’AN DAN PEMBERIAN AROMA TERAPI BUNGA MAWAR TERHADAP KUALITAS TIDUR MALAM PADA ANAK UMUR 3-5 TAHUN - ULVA NOVIANA; HENI EKAWATI (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2020)
Sleep quality is a child's ability to sleep with good quality covering length, time, frequency of waking and depth and sleep reviews. Based on Preliminary study in the village of Gebbang Bangkalan District on 4th January 2020 there were 10 children, obtained data that 2 children have a good sleep quality, 2 children sleep quality enough, and 6 children including less sleep quality. The purpose of the study is to determine the effect of giving the aroma therapy to sleep quality in children aged 3-5 years. This research used Quasy Experiment design with a two group pre-test-post test design approach. The Variable Independennya Relaxation technique murotal al-Qur'an and giving aroma therapy for roses while The dependent variable was sleep quality. The population number was18 children with a sample of 9 students of the treatment group and 9 students of the control group are taken non-probability purposive sampling. This research was conducted in the village of Gebbang Dusun, Bangkalan regency. In April 2020 and a statistical test used the Wilcoxon test with a = 0.05. The results of the research get that on the treatment group of sleep quality in children aged 3-5 years based on the Wilcoxon statistical test showed that p value = 0.008, while in the control group that is not given Murotal al-Qur'an and aroma therapy Bungan rose shows the results that p value = 0.397, Mann-Whitney test shows the results that p value = 0.001, so that it can be concluded that there is a therapeutic influence Murotal al-Qur'an and the aroma of rose therapy to sleep quality in children aged 3-5 years. Based on this research it is advisable for parents to play Murotal al-Qur'an and do the aroma therapy, performed at night when the child is asleep, to improve the sleep quality of children aged 3-5 years in the village of Gebbang Hamlet, Bangkalan Regency.